The Mongolian and Dashti Kipchak Begs Under Sultan Ahmad and Sultan Mahmud Mirza - Makhmudov Uktamjon Mukhsinjan ugli (Genius Journals, 2024)
In this article, general opinions are given about Dashti Kipchak and Mongolian begs and army, who served Ahmad Mirza and Mahmud Mirza, the sons of Sultan Abusaid Mirza.
Keywords: Sultan Ahmad Mirza; Mahmud Mirza; Mahmud Khan Babur